The Transcendental Description of Karmic Experience——"Interpretation" as an Organic Life System (Journal of humanities and social sciences exploratio, 2026)
Based on the organic life system of the "I" as the interpreter, this paper aims to explore the karmic structure of interpretive activity. The article begins by apprehending "Being" as "Emptiness (Śūnyatā)," grounding it as an ontology with the karmic organism (机缘整体) as the sole transcendental, thereby describing how existents subsist in the "non-obstruction between principle and phenomena (理事无碍)" and the "non-obstruction between phenomenon and phenomenon (事事无碍)." On this basis, it further introduces "the Problem (问题)" as the key horizon through which existents attain their distinctive being from the interpenetrating coexistence within the undifferentiated whole, pointing out that "the Problem," through its either-or decisional structure, enables existents to acquire their own differentiatedness and become their own lifefulness (生命性). Consequently, interpretation is understood as a kind of life-karma (生命机缘) belonging to the "I's" "Problem." It is the authentic activity of the "I" interpenetrating with all things within the karmic organism, responding to the demand of "the Problem." It is an activity (life-karma) of describing karmic experience within the karma of "the Problem," whose foundation lies in carrying the life of both the "I" and all things, serving as an existential concern for the "how-to-be (coexistence)" of all things having their own distinctive being within coexistence.
Keywords: Organic life system; Interpretation; The "I"; Karmic organism; Karmic experience